2021
DOI: 10.1038/s41586-021-03362-0
|View full text |Cite
|
Sign up to set email alerts
|

NASH limits anti-tumour surveillance in immunotherapy-treated HCC

Abstract: Hepatocellular carcinoma (HCC) can have viral or non-viral causes1–5. Non-alcoholic steatohepatitis (NASH) is an important driver of HCC. Immunotherapy has been approved for treating HCC, but biomarker-based stratification of patients for optimal response to therapy is an unmet need6,7. Here we report the progressive accumulation of exhausted, unconventionally activated CD8+PD1+ T cells in NASH-affected livers. In preclinical models of NASH-induced HCC, therapeutic immunotherapy targeted at programmed death-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
808
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 855 publications
(936 citation statements)
references
References 70 publications
22
808
2
3
Order By: Relevance
“…In a meta-analysis by P ster, patients with a viral etiology showed therapeutic bene ts with ICI treatment [HR 0.64], whereas those with nonviral etiology HCC did not [HR 0.92] (P=0.03) 5 . That study also presented results of two different validation studies of ICI treatment for HCC, in which NAFLD-HCC cases showed signi cantly worse OS than HCC with other etiology (HR 2.6 95%CI 1.2-5.6, P=0.017; median 8.8 vs. 17.7 months, P=0.034) 5 . In patients undergoing ICI treatment, background liver disease etiology might be a biomarker ofe cacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis by P ster, patients with a viral etiology showed therapeutic bene ts with ICI treatment [HR 0.64], whereas those with nonviral etiology HCC did not [HR 0.92] (P=0.03) 5 . That study also presented results of two different validation studies of ICI treatment for HCC, in which NAFLD-HCC cases showed signi cantly worse OS than HCC with other etiology (HR 2.6 95%CI 1.2-5.6, P=0.017; median 8.8 vs. 17.7 months, P=0.034) 5 . In patients undergoing ICI treatment, background liver disease etiology might be a biomarker ofe cacy.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the good therapeutic response noted for Atezo+Bev in the IMbrave 150 trial, a recent report noted that therapeutic responses to ICI treatments differed according to the etiology of the background liver disease 5 . Meta-analysis of that report 5 indicated that patients with HCC with a viral etiology showed therapeutic bene ts from ICI use [HR 0.64], whereas those with a nonviral etiology did not [HR 0.92] (P=0.03).Most importantly, results of two validation cohorts treated with ICI clearly showed that overall survival (OS) for non-alcoholic fatty liver disease or non-alcoholic steatohepatitis (NAFLD/NASH)related HCC patients was signi cantly worse than that for the non-NAFLD/NASH-related HCC group (11.0 vs. 5.4 months, P=0.023 and 17.7 vs. 8,8 months, P=0.034, resspectively) 5 . This is the rst epoch-making and striking results that ICI treatment response differs based on background liver disease etiology, especially NASH/NAFLD related HCC lacks immune response and immune surveillance to the tumor associated antigen.…”
Section: Introductionmentioning
confidence: 96%
“…Although none has yet been compiled for NASH-HCC, similar efforts are underway and are likely to uncover novel, actionable targets for chemopreventive or treatment strategies in individuals at high risk or those with HCC. Recent mouse models and clinical data indicate that NASH-HCC is less responsive to emerging immunotherapies because of reduced infiltration of CD4 + T cells, impaired immune surveillance, and NASH-related aberrant T cell activation, which induces tissue damage (Heinrich et al, 2021;Pfister et al, 2021).…”
Section: Reviewmentioning
confidence: 99%
“…Last but not least, the efficacies of ICIs in HCCs of different etiologies should be clarified, in particular in non-alcoholic steatohepatitis (NASH) [115]. In a recent metaanalysis of the results of the CheckMate-459, IMbrave150, and Keynote-240 trials, non-viral (alcoholic or NASH) patients had no superior survival compared to the control arms, unlike HBV/HCV-related HCC patients [115]. Furthermore, non-alcoholic fatty liver disease (NAFLD) was independently associated with shortened median OS after immunotherapy.…”
Section: The Future Development Of Ici Combinationsmentioning
confidence: 99%